Vocational Stability for Educational Guides in Basrah Governorate - Dayekh, Khalaf (Pubmedia Jurnal Pendidikan Olahraga, 2024)
Current research aims to identify vocational stability for educational guides in Basrah Governorate, where research community included educational guides in service in government schools, and to achieve research aim, researcher chose a sample consisting of (200) mentors and Guides , researcher used a questionnaire (research tool) It consisted of (20) paragraphs, extracted from vocational stability literature , and it was presented to a group of experts and arbitrators to extract its apparent honesty, to measure existence of characteristic or apparent or not, and percentage of acceptance of paragraph was based on (80 %) or more, where all paragraphs won On required percentage, and for purpose of completing validity of construction, researcher applied scale on research sample to extract distinctive strength of scale vertebra For paragraphs, where several paragraphs that get a calculated, calculated value (1.96) and more statistically indicate at level of significance (0.05) and degree of freedom (106), and it appeared that all paragraphs were distinct because calculated Total values ​​are greater than Table value (1.96), and it has results of statistical analysis indicate that educational guides in general have high vocational stability at work.